Human Milk, More Than Simple Nourishment - Giulia Vizzari; Daniela Morniroli; Federica Ceroni; Elvira Verduci; Alessandra Consales; Lorenzo Colombo; Jacopo Cerasani; Fabio Mosca; Maria Lorella Giannì (MDPI AG, 2021)
Human breast milk not only has nutritional properties but also holds a functional role. It contains various bioactive factors (lactoferrin, lysozyme, leukocytes, immunoglobulins, cytokines, hormones, human milk oligosaccharides, microbiome, microRNAs and stem cells) shown to contribute to several short- and long-term health outcomes. Some of these factors appear to be involved in the infant's neuro-cognitive development, anti-oncogenic processes, cellular communication and differentiation. Furthermore, breast milk is increasingly recognized to have dynamic characteristics and to play a fundamental role in the cross-talking mother-neonate. This narrative review aims to provide a summary and an update on these bioactive substances, exploring their functions mainly on immunomodulation, microbiome and virome development. Although the knowledge about breast milk potentiality has significantly improved, leading to discovering unexpected functions, the exact mechanisms with which breast milk exercises its bioactivity have not been completely clarified. This can represent a fertile ground for exploring and understanding the complexity behind these functional elements to develop new therapeutic strategies.